1998
DOI: 10.1111/j.1348-0421.1998.tb02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Dissemination by Intrarectal Infection with Listeria monocytogenes in Mice

Abstract: Orally ingested Listeria monocytogenes is known to penetrate into Peyer's patches (PP) and translocate to the spleen and liver. Herein, extraintestinal dissemination of the bacterium independent of PP was investigated. Dissemination of Listeriae to the spleen and liver was observed in intrarectally infected mice as well as in intragastrically infected animals in spite that no Listeriae were detected in the small intestines of mice infected intrarectally. Decreased numbers of intestinal intraepithelial lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…This range is comparable to previously reported doses used in animal models of oral listeria infection (17,24,26). Viability and the exact number of L. monocytogenes cells in the inocula were determined by plating on PALCAM.…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…This range is comparable to previously reported doses used in animal models of oral listeria infection (17,24,26). Viability and the exact number of L. monocytogenes cells in the inocula were determined by plating on PALCAM.…”
Section: Methodssupporting
confidence: 74%
“…To study the efficacy of food components, an animal model of food-derived listeriosis with a quantitative, reliable, and accurate biomarker for translocation is required. Translocation of L. monocytogenes is observed in rats (24,28) and mice (26), making them suitable models. Classically, translocation of listeria in animal models is determined by microbiological culturing of lymphoid organs (24,26,28).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2). Similarly, our previous study showed that bacterial growth in livers and spleens began on day 2 when L. monocytogenes infection was induced by an oral route (23,25). These results suggest that L. monocytogenes can finally result in systemic infection irrespective of routes of invasion.…”
Section: Discussionmentioning
confidence: 99%